Basal FSH values are positively associated with aneuploidy incidence in pre-advanced maternal age (AMA) but not in AMA patients - Jacobs, Catherine K.; Nicolielo, Mariana; Alegretti, José Roberto; Canto, Mariabeatrice Dal; Renzini, Mario Mignini; De Ponti, Elena; Chehin, Mauricio Barbour; Motta, Eduardo L. A.; Lorenzon, Aline R.; Buratini, Jose [UNESP] (My University, 2024)
Purpose: To assess the impact of maternal age on the association between maternal basal FSH and aneuploidy. Methods: A retrospective study including data from 1749 blastocysts diagnosed as euploid or aneuploid by PGT-A (preimplantation genetic testing for aneuploidy). Aneuploidy incidence was compared between embryos from mothers with high vs. low basal FSH levels (above and below the group median, respectively) in total, pre-AMA (advanced maternal age; < 35 years, 198 embryos) and AMA (≥ 35 years, 1551 embryos) patient groups, separately. To control for the interference of potentially confounding variables, the association between aneuploidy and high basal FSH levels was assessed by multivariate logistic analysis in overall, pre-AMA and AMA patient groups. Results: Overall, aneuploidy rate was 9% higher (p = 0.02) in embryos from patients with high basal FSH (63.7%) compared to those with low basal FSH (58.4%). In the pre-AMA subgroup, aneuploidy incidence was 35% higher (p = 0.04) in embryos from patients with high basal FSH (53.5%) compared to those with low basal FSH (39.4%). Differently, aneuploidy occurrence did not vary between embryos from AMA patients with low (61.0%) and high (64.8%) basal FSH (p = 0.12). The multivariate analysis revealed that, in pre-AMA embryos, the association between aneuploidy occurrence and high basal FSH is independent of potential confounding variables (p = 0.04). Conclusion: Maternal basal FSH values are associated with embryo aneuploidy in pre-AMA but not in AMA patients. The present findings suggest that basal FSH is a useful parameter to assess aneuploidy risk in pre-AMA patients and reinforce the hypothesis that excessive FSH signalling can predispose to oocyte meiotic errors.
Keywords: Advanced maternal age; Aneuploidy; Basal FSH; PGT-A